(3QSGdI JhHjN Sgds - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN GdaGVd GdKbI GdCejf GdeaUM Yf Ydeg haVGFdg GdOGd HeVehf ebGhdg Ydi UMg eNGFdg s
(3BNQgG (B:s
(3dCf dg ai GdHYK faG YdjeI JUjQ Edi GdaQOhS MVQg NUeg hUQYg Cgd GdHZi JGfi HZJI aef cGf efge jSJYO dbUeg fLRJ HefI hdi GdBNQI Je JhHjN Sgd hGdMeO dehdGfG hMOg hGdTcQ ddEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B79s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis